Outpatient Prescriptions of Kampo Formulations in Japan - Yamana, Hayato (Intern Med, 2020)
OBJECTIVE: Kampo is a traditional Japanese medicine using formulae of natural agents. Although Kampo is widely practiced, information regarding the current prescriptions of Kampo formulations is lacking. The aim of the study was to describe the outpatient use of Kampo formulations in the current Japanese health insurance system. METHODS: From the JMDC Claims Database, we identified subscribers with outpatient prescriptions of Kampo extract formulations between April 2017 and March 2018. Prescription records were summarized at the individual level to describe the pattern of each formula's use, such as the frequency of prescription and the number of days within a year that were covered by the prescriptions. We also examined whether or not Kampo formulations were prescribed in combination with other drugs. RESULTS: Of the 4.5 million subscribers, 13.5% received prescriptions of Kampo extracts within 1 year, and 54% of Kampo users were women. The most commonly prescribed Kampo formulae included kakkonto, shoseiryuto, and maoto, which were used for the short term covering a median of 5 to 7 days. There were also several formulae that were prescribed for longer periods. The median numbers of days covered by kamishoyosan and keishibukuryogan were 60 and 56, respectively. Kampo formulations were used in combination with Western drugs in 85% of prescriptions. CONCLUSION: Kampo formulations are commonly prescribed under the Japanese insurance system and are frequently used in combination with Western drugs. The pattern of prescriptions varied across different formulae.